Cyclosporine vs. tacrolimus after liver transplantation for primary sclerosing cholangitis – a propensity score-matched intention-to-treat analysis - Åberg, Fredrik; Sallinen, Ville; Tuominen, Samuli; Adam, René; Karam, Vincent; Mirza, Darius; Heneghan, Michael A.; Line, Pål-Dag; Bennet, William; Ericzon, Bo-Göran; Grat, Michal; Lodge, Peter; et al. (Journal of hepatology, 2024)
There is controversy regarding the optimal calcineurin inhibitor type after liver transplant(ation) (LT) for primary sclerosing cholangitis (PSC). We compared tacrolimus with cyclosporine in a propensity score-matched intention-to-treat analysis based on registries representing nearly all LTs in Europe and the US. From the European Liver Transplant Registry (ELTR) and Scientific Registry of Transplant Recipients (SRTR), we included adult patients with PSC undergoing a primary LT between 2000-2020. Patients initially treated with cyclosporine were propensity score-matched 1:3 with those initially treated with tacrolimus. The primary outcomes were patient and graft survival rates. The propensity score-matched sample comprised 399 cyclosporine-treated and 1,197 tacrolimus-treated patients with PSC. During a median follow-up of 7.4 years (IQR 2.3-12.8, 12,579.2 person-years), there were 480 deaths and 231 re-LTs. The initial tacrolimus treatment was superior to cyclosporine in terms of patient and graft survival, with 10-year patient survival estimates of 72.8% for tacrolimus and 65.2% for cyclosporine (p <0.001) and 10-year graft survival estimates of 62.4% and 53.8% (p <0.001), respectively. These findings were consistent in the subgroups according to age, sex, registry (ELTR vs. SRTR), time period of LT, MELD score, and diabetes status. The acute rejection rates were similar between groups. In the multivariable Cox regression analysis, tacrolimus (hazard ratio 0.72, p <0.001) and mycophenolate use (hazard ratio 0.82, p = 0.03) were associated with a reduced risk of graft loss or death, whereas steroid use was not significant. Tacrolimus is associated with better patient and graft survival rates than cyclosporine and should be the standard calcineurin inhibitor used after LT for patients with PSC. The optimal calcineurin inhibitor to use after liver transplantation in patients with primary sclerosing cholangitis has yet to be firmly established. Since randomized trials with long follow-up are unlikely to be performed, multicontinental long-term registry data are essential in informing clinical practices. Our study supports the practice of using tacrolimus instead of cyclosporine in the initial immunosuppressive regimen after liver transplantation for patients with primary sclerosing cholangitis. The retrospective registry-based design is a limitation. [Display omitted] •Tacrolimus was associated with superior survival compared to cyclosporine after liver transplantation for PSC.•10-year patient survival estimates were 73% for tacrolimus and 65% for cyclosporine.•10-year graft survival estimates were 62% for tacrolimus and 54% for cyclosporine.•Findings were consistent across subgroups by age, sex, registry, time period of LT, MELD score, and diabetes status.•Tacrolimus emerges as the preferred calcineurin inhibitor after liver transplantation for PSC.